REKABENTUK MODEL SISTEM GUNA SEMULA AIR WUDHUK - Abd Rahman, Misbahul Muneer; Kaami, Masiri; Mohamad, Mahmod Abd Hakim; Mohmad Omar, Mohamad Hanif; Mohamed Nor, Mohd Hadri; Abd Aziz, Azizul Rahman (Journal of Techno-Social, 2014)
Ablution is an essential practice as a Muslim because it is an abligatory requiredto perform prayer. A Muslim use approximately 5 litres of water per singleablution. Approximately, a Muslim use 25 litres of treated water to performablution. Islam categorized the used water produced from an ablution asMusta’mal water. Normally Musta’mal water will be left to flow into the drainagesystem. The accumulated amount of wasted water is significant when it ismeasured at a mosque or surau. The quality of Musta’mal water is far better than the typical quality of the waste water produced from washing activities because there were no oil, grease, soap and dirt except for small quantities ofmiccroorganisms. To overcome this problem, this study focused on thediscussion of reusing ablution water based on Shari’ah law which led to thedevelopment of a system (or model) to reuse ablution water. This ablution water reuse system consists of several parts including ablution water collection tanks, filters, storage tanks, filling tank, water pump and water sensor. This system runs automatically using a water pump and water sensor. The study found that the Shari’ah law allow reuse water to be used again as ablution water. Based on this study, it is found that the ablution water reused system is feasible and is able to be produced from the engineering aspect.